Degradation of torsional behaviors of 3-D braided thin-walled tubes after atmospheric thermal ageing. (January 2022) - Xun, Limeng; Wu, Yuanyuan; Huang, Shuwei; Sun, Baozhong; Gu, Bohong; Hu, Meiqi
Abstract: Degradations of torsional behavior is a key issue to the evaluation of the 3-D braided tubes in thermal-oxidizing environment for a long-term service. Here we report the effect of thermal oxygen ageing on torsional behaviors of 3-D carbon fiber/ epoxy resin braided composite tubes. The torsional behaviors of the 3-D braided tubes were quasi-statically tested after ageing at 110 °C and 180 °C for 8, 16 and 32 days respectively. Three-dimensional digital image correlation (3D-DIC) technique was used to display shear strain distribution. A microstructure finite element analysis (FEA) model was established to reveal the torsional damage mechanisms. We found that both temperature rise and ageing time extension will decrease the shear modulus and torque strength. Temperature has a greater influence on modulus and torque strength degradation than ageing time does. Ageing at 110 °C, resin crack and yarn breakage are the main torsional damages, while at 180 °C, yarn pull-out emerges as a further torsional damage. Highlights: Degradation of torsion strength of 3-D braided tube after atmospheric thermal aging. Torsional damages and shear strain distributions after different aging conditions. Influences of aging temperatures and time on torsional damage mechanisms.